Exploring Students' Knowledge about Hand Washing with Soap Through Video Media at Middle School - Pustika, Dinda Dwi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to evaluate the effectiveness of using video media in increasing students' knowledge and attitudes about the importance of washing hands with soap at Public Middle School 31 North Bengkulu Methodology: This research uses quantitative methods with a pre-experimental One Group Pretest-Posttest Design. The research population was class III students at Public Middle School 31 North Bengkulu, with a sample of 35 students selected using a purposive sampling technique. Data analysis was carried out using the Wilcoxon test to test the difference between pretest and posttest results. Main Findings: This study concludes that the use of video media as a health promotion tool significantly increases the knowledge and attitudes of students at Public Middle School 31 North Bengkulu towards the importance of washing hands with soap. Video media is proven to be more effective than conventional methods in attracting attention and increasing student participation during the learning process Novelty/Originality of this study: This research is very urgent considering the high rate of transmission of infectious diseases among adolescents which can have a significant impact on their health and school attendance. Infectious diseases such as flu, diarrhea and respiratory infections often spread quickly in the school environment, causing high levels of absenteeism and reducing learning productivity.